(untitled) (Journal of Science and Technology, 2016)
In valuing property one method that is commonly adopted in situations where market evidence is non-existent is the Depreciated Replacement Cost method. As the name suggests, this involves estimating the replacement cost as new of the property, which is the subject matter of the valua- tion, and making allowances for accrued depreciation. The allowance made for depreciation is important as it allows for the estimation of value that reflects the current state of the property. The estimation of depreciation for valuation purposes has been the subject for a number of em- pirical studies. There is however no consensus within the valuation profession as to which ap- proach to estimating accrued depreciation addresses the key elements that are of concern to the valuer viz; age, condition and functional obsolescence. The paper proposes one such approach that incorporates all these elements in the estimation of accrued depreciation for valuation pur- poses. The approach first considers the individual causes of depreciation separately and uses different methods to estimate accrued depreciation for each of the causes of depreciation. Total accrued depreciation is then estimated by first taking account of curable physical depreciation and then age and functional obsolescence. The approach proposed presents a basis for a more comprehensive discussion and a subsequent adoption of a common methodology valuers can rely on to estimate depreciation.